TRIGGER OF IMPOLITENESS LANGUAGE IN POLITICAL COMMENTS ON SOCIAL MEDIA - Ambarita, Rosmita (Fakultas Sastra UMN AL Washliyah, 2024)
This current study is concerned with cyber pragmatics that analyzes the trigger of language impoliteness on social media, which is used by netizens in political comments. Instagram and Facebook are the media interactions that contain impolite comments. The main theory used in this study is impoliteness theory pioneered by Culpeper (2011) which explains that impoliteness is communication behavior that intends to attack the face of the interlocutor. The method used is a qualitative method. Data is collected using note-taking techniques through screen capture and data is obtained through a questionnaire in the form of a Google form. The results of data analysis based on the most dominant or first triggering factor were criticized with 36% (n=36), factors showing feelings of disappointment as much as 31% (n=31) with political discourse in different situations. The third trigger factor is a form of incongruity as much as (n=17), then the fourth trigger factor is as dislike as much as (n=7), the fifth trigger factor is as a result of anger as much as (n=4), the sixth trigger factor is forms of incompatibility as many as (n=3), and the least frequency of triggering factors are forms of distrust and annoyance respectively as many as (n=1). Based on the results of data analysis from the research problem, there are several functions of linguistic impoliteness, namely to criticize, be sarcastic, and express anger and disappointment.